Studies on Nutritional Components, Antioxidant Activities and Microbial Load in Simple Processed Product Developed from Banana (cv. Bhimkol) - Das, Priyanka; Devi, Ramala; Dutta, Archana Singha; Boro, Robin Chandra; Sarmah, Tarun Chandra (Asian Journal of Chemistry, 2015)
Banana (cv. Bhimkol) fruit is considered as a good natural source of food among the rural masses of North Eastern region of India. However, the processed form of this fruit is very negligible. Considering nutritional status of the fruit and to impart place, consumer and form utility, a dehydrated powder was prepared, to which primary preservative added (sugar) and stored in glass container. The mineral content (nitrogen, potassium, calcium, iron and phosphorus), microbial load and antioxidant activity were determined up to six months of storage, both at refrigerated condition and room condition. The result showed better retention of minerals and antioxidant activities in refrigerated condition than in room storage. Result of the microbial count did not show any health hazard.